Development of Interactive Media Using Articulate Storyline Based on Banten Local to Improve IPAS Learning Outcomes of Elementary School Student - Faiz, Muhammad; Dewi, Ratna Sari; Sari, Indah Juwita (FKIP - Universitas Riau, 2025)
This study aims to examine the stages of development, effectiveness, and student responses to Banten local wisdom-based interactive picture story media to improve IPAS learning outcomes of fourth grade students of SDN Kebaharan 1. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research was motivated by student boredom in learning IPAS, lack of integration of local wisdom, and low learning outcomes. The results showed that the interactive media developed effectively improved learning outcomes, with an N-Gain value of 77% in the effective category. Student response to the media with a value of 79% is classified as good. Validation by material experts showed a feasibility percentage of 86.5%, and media expert validation of 79%, both of which were declared feasible. Thus, this interactive media is effective and feasible to use as a learning tool for IPAS in class IV SDN Kebaharan 1 Serang City.